Human Versus Corporate Tone of Voice: Which one Performs Better in The Telecommunication Industry? - Wawas Bangun Tegar Sunaryo Putra; Karinka Bella Prasetya; Jolyanto Jolyanto (University of Merdeka Malang, 2024)
This research delves into the nuanced impact of human and corporate tones of voice on perceived social presence, trust, and customer satisfaction, contrasting the communication strategies between the human tone of the voice-centric brand (HCB) and corporate tone of the voice-centric brand (CCB), two notable brands in the Indonesian market. Using the PLS-MGA technique, the study offers detailed insights into the real-world implications of these tones through two distinct case studies. Findings reveal a marked difference between HCB and CCB concerning the influence of tone on perceived social presence. HCB's human tone resonates more with customers, creating a pronounced positive impact, while CCB's corporate tone also has a positive but lesser influence. In shaping customer trust, the human tone in HCB stands out. However, when it comes to satisfaction, only HCB's human tone remains influential, with CCB's corporate tone not manifesting a significant effect. The study further underscores the nuanced role of perceived social presence as a mediator in the relationship between tone of voice, trust, and satisfaction. An essential takeaway is that while the human tone is often lauded for its benefits, it is only sometimes suitable. Industries prioritizing professionalism and expertise might need a balanced approach between human and corporate tones. The findings, especially contextualized within the two Indonesian network providers, emphasize the necessity of recognizing and catering to diverse customer expectations.